Pengaruh Kepercayaan dan Promosi Terhadap Keputusan Pembelian Konsumen Pada MarketPlace Lazada Di Cikarang Selatan - Riyanto, Ahmad; Syahrial Yusuf, Muhammad (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to find out and analyze how much the influence of Trust and Promotion have on Purchasing Decisions at the Lazada MarketPlace in South Cikarang. This research method uses a quantitative approach were consumers who had used the Lazada MarketPlace in South Cikarang 1 and 2 times, or more and there were 135 respondents. The sampling technique for this recearch used Accidental Sampling. Data analysis in this study used multiple linear regression. This research shows that Trust (X1) partially has a positive and sinificant effect on Consumer purchasing Decisions (Y) at the Lazada MarketPlace in South Cikarang by 28.0%. Promotion (X2) partially has a positive and significant effect on consumer Purchasing Decisions (Y) at the Lazada MarketPlace in South Cikarang by 36.5%, and jointly Trust (X1) and Promotion (X2) have a positive and significant effect on Purchasing Decisions (Y) Consumers at the Lazada MarketPlace in South Cikarang were 41.9%, while the remaining 58.1% were influenced by other variables not examined in this research. The results of this research are that trust and promotion have a significant effect on purchasing decisions, both partially and simultaneously